Entrepreneurial leadership competencies development among Malaysian university students: the pervasive role of experience and social interaction - Bagheri, Afsaneh; Lope Pihie, Zainatul Akmaliah (Universiti Putra Malaysia Press, 2012)
Recent developments in entrepreneurial leadership have raised many questions about how to develop entrepreneurial leadership competencies, particularly among university students. This qualitative research attempts to answer some questions on entrepreneurial leadership competencies development among university students. In more specific, this paper provides deeper insights into the mechanisms through which students learn and develop their entrepreneurial leadership competencies. Fourteen undergraduate students who successfully involved in leading entrepreneurial clubs and projects in university entrepreneurship programmes were purposefully selected as the participants. Semistructured interviews were then conducted to determine how the participants had developed their entrepreneurial leadership. Our findings revealed that students’ entrepreneurial leadership was developed through a dynamic and continuous process of experiential and social interactive learning. In addition to availability, a variety of leadership experiences and social interactions influence students’ entrepreneurial leadership learning and development. Meanwhile, implications of the findings to entrepreneurial leadership education and practice, as well as areas for future research are also discussed.